The handbook for student leadership development - Komives, Susan R., 1946- (San Francisco : Jossey-Bass, 2011)
"This is a comprehensive handbook provides essential research, theoretical framing, and practical guidance to help higher education practitioners develop, advance, and sustain a student leadership program. This new and thoroughly revised edition introduces a model for designing and executing any student leadership program, which will serve as a framing device for the book. This model covers: Foundations of Leadership Education, Program Design, Program Context, and Program Delivery. In addition, the book includes a rich, organized array of further recommended resources that will be connected to elements in various chapters."--
Includes bibliographical references and indexes.
Keywords: Student affairs services -- United States -- Handbooks, manuals, etc; College student development programs -- United States -- Handbooks, manuals, etc; Counseling in higher education -- United States -- Handbooks, manuals, etc; EDUCATION / Students & Student Life